Brucella suis bacteremia misidentified as Ochrobactrum anthropi by the VITEK 2 system - Andrea Vila; Hugo Pagella; Gonzalo Vera Bello; Alicia Vicente (Journal of Infection in Developing Countries)
Ochrobactrum and Brucella are genetically related genera of the family Brucellaceae, sharing 98.8% rRNA similarity. Because of their phenotypic similarity, Ochrobactrum can be miscoded as Brucella by automated identification systems. The misidentification on blood cultures (BCs) of B. suis as O. anthropi by the VITEK 2 system is herein described. A 67-year-old male with a prosthetic mitral valve and fever was admitted with bacteremia due to a Gram-negative coccobacillus identified as O. anthropi by VITEK 2. The patient’s fever persisted along with positive blood cultures despite specific antimicrobial treatment. Due to this adverse outcome, the patient was interrogated again and admitted having domestic swine. Serological tests were positive for acute brucellosis. Polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) of BC strains identified B. suis biovar 1. Timely identification of Brucella is essential for providing proper treatment to the patient and for advising safe handling of laboratory cultures in biological safety cabinets to prevent laboratory-acquired infection. Countries where brucellosis is endemic must be aware of this possibility.